Aktivitas Antibakteri Kombinasi Ekstrak Etanol Daun Belimbing Wuluh (Averrhoa Bilimbi L.) Dan Daun Sirih Hijau (Piper Betle L.) Terhadap Bakteri Staphylococcus Aureus - Anindya, Yuarinda Melly; Rejeki, Desi Sri; Nurhidayati, Lailiana Garna; Fakhrunnisa, Farida (PT. Pubsains Nur Cendekia, 2024)
Wuluh starfruit (Averrhoa bilimbi L.) and green betel (Piper betle L.) leaves are medicinal plants that have antibacterial properties. Medicinal plants can be used as alternative medicine to obtain new compounds as antibacterial. The chemical compounds in wuluh starfruit leaves that have antibacterial properties are flavonoids, saponins and tannins, while green betel leaves have flavonoids, saponins, tannins and essential oils. The study aimed to determine the antibacterial activity of a combination of wuluh starfruit and green betel leaves extract against the growth of Staphylococcus aureus. The experimental research used a diffusion method by disc paper based on the diameter of the inhibition zone or the clear area formed around the paper disc. The extracts were obtained by maceration method using 96% ethanol solvent. The values of the inhibition zone in four concentrations; 5%, 10%, 15%, and 20% were respectively 13 mm, 13.5 mm, 15 mm, and 16 mm. On the other hand, the concentration of 20% had the most effective inhibition zone with a strong category against Staphylococcus aureus.